Modification of Eclipse simulator for microbial enhanced oil recovery - Bashirul Haq; Jishan Liu; Keyu Liu; Esmile Malaki; Dhafer Al-Shehri (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract Many widely used reservoir simulators include an EOR option, but there is no feature available in a commercial simulator in the oil industry that simulates microbial enhanced oil recovery (MEOR) process. Eclipse, one of the popular reservoir simulators, does not have this option. In this study the Eclipse reservoir simulator has been modified and used to simulate MEOR core-flooding experiments. The combined effects on oil recovery of anionic surfactants and alcohol, nonionic surfactants and alcohol, and anionic and nonionic surfactants blended with alcohol are examined. A commercial Eclipse simulator was modified to add the option to simulate a MEOR process as this was not available. The modified simulator was used to simulate three core-flood experiments with three formulations. The JF-2 bio-surfactant and butanol solution core-flood test was simulated. The result was slightly higher than the experimental result but compared reasonably well. The simulated tertiary and total oil recoveries of the APG and butanol solution were similar to the experimental values: the simulated TOR and total recovery were 41% and 81%, respectively, while the core-flooding TOR and total recovery were 41% and 82%. The APG, bio-surfactant and butanol combination core-flood experiment, when simulated, produced an oil recovery curve that was a reasonable match with the experimental curve.